Impact of COVID-19 outbreak on nurses’ mental health: a prospective cohort study - Sampaio, Francisco (2021)
Objectives: To evaluate variations in nurses’ sleep quality and symptoms of depression, anxiety and stress during the COVID-19 outbreak, and to evaluate whether the presence of potential risk factors influenced these symptoms over time. Methods: This prospective cohort study surveyed nurses three times – surveying personal factors, working conditions, family dynamics, and attitude towards COVID-19 – between March 31 and May 4, 2020. Nurses’ mental health was assessed through Depression Anxiety Stress Scales – short version (DASS-21); their sleep quality was assessed through a 5-point Likert scale question. Results: Nurses' sleep quality and symptoms of depression, anxiety and stress presented a positive variation over the COVID-19 outbreak. The only factors which are directly related to the COVID-19 outbreak and that were associated with the positive variation in nurses’ symptoms of depression, anxiety and stress were the fear to infect others and the fear to be infected (higher fear of being infected or to infect someone corresponded to increased symptoms of depression, anxiety and stress). Conclusions: Although the COVID-19 outbreak seems to have had an immediate impact on nurses' mental health, a psychological adaptation phenomenon was also observed. Future research should focus on assessing nurses’ symptoms of depression, anxiety and stress, after the COVID-19 pandemic, in order to compare and contrast the findings with the results of our study.